R&D Performance in the Pharmaceutical Industry: A Case Study of Egypt - AlAyouty, Iman (European Journal of Sustainable Development, 2017)
In Egypt, knowledge production function estimation using firm-level panel data indicates weak R&D performance in pharmaceutical firms. At the micro-level, in-depth interviews with selected pharmaceutical firms reveal a low R&D intensity, in addition to an inconsistent pattern of spending over time. Firms undertake piecemeal research projects, thus lacking a long term research vision. They put greater emphasis on R&D of the ‘development’ rather than the ‘basic’ or ‘applied’ types. Other symptoms of weakness are: modest collaboration with universities in research; modest collaboration with other firms in research and/or intellectual property; and a poor capacity to innovate. At the macro level, the public R&D system lacks good governance and sound coordination between research institutions. At both micro- and macro-levels, R&D efforts hinder innovation, thus hindering Egypt’s sustainable development and integration in today’s knowledge-based economy. Keywords: research and development, output, pharmaceutical industry, knowledge production function, in-depth interviews